Mobile Computing For Pest And Disease Management Using Spectral Signature Analysis: A Review - Nik Norasma Che’Ya; Nur Adibah Mohidem; Nor Athirah Roslin; Mohammadmehdi Saberioon; Mohammad Zakri Tarmidi; Jasmin Arif Shah; Wan Fazilah Fazlil Ilahi; Norsida Man (Multidisciplinary Digital Publishing Institute, 2024)
Volume: 12 Issue: 4 (page: 1-22)